2010
DOI: 10.1002/jmri.22383
|View full text |Cite
|
Sign up to set email alerts
|

Recent technological and application developments in computed tomography and magnetic resonance imaging for improved pulmonary nodule detection and lung cancer staging

Abstract: This review compares the emerging technologies and approaches in the application of magnetic resonance (MR) and computed tomography (CT) imaging for the assessment of pulmonary nodules and staging of malignant findings. Included in this review is a brief definition of pulmonary nodules and an introduction to the challenges faced. We have highlighted the current status of both MR and CT for the early detection of lung nodules. Developments are detailed in this review for the management of pulmonary nodules usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 144 publications
1
47
0
2
Order By: Relevance
“…Despite all efforts, lung cancer remains a challenging disease to effectively identify, diagnose, and treat. Its 5-year survival rate remains similar to that of 15 years ago at 13% for all stages (clinical staging) [ 2 ] . Thus, it is imperative to develop new algorithms and techniques for the characterization of lung nodules and staging of lung cancer.…”
Section: Introductionmentioning
confidence: 73%
“…Despite all efforts, lung cancer remains a challenging disease to effectively identify, diagnose, and treat. Its 5-year survival rate remains similar to that of 15 years ago at 13% for all stages (clinical staging) [ 2 ] . Thus, it is imperative to develop new algorithms and techniques for the characterization of lung nodules and staging of lung cancer.…”
Section: Introductionmentioning
confidence: 73%
“…There are many different dynamic MR protocols for the differential diagnosis of pulmonary nodules, with sensitivities ranging from 94%-100%, specificities ranging from 70%-96%, and accuracies greater than 94%. 37 Alper et al 38 found that early peak and maximum peak were significantly higher in malignant nodules than in benign ones. Malignant nodules less than 3 cm usually manifested with homogeneous and apparent enhancement.…”
Section: Tissue Characterization Of Lung Nodule or Massmentioning
confidence: 97%
“…45 CT has sensitivity ranging from 40%-84% and specificity of 57%-94% in the assessment of mediastinal invasion. 37 The absence of fat planes in T1W images is useful in determining invasion. STIR sequence can also depict adjacent structure invasion with marked high SI, in contrast to the routine T1W and T2W imaging.…”
Section: Staging Of Lung Cancermentioning
confidence: 99%
“…Nevertheless, the major challenges to pulmonary MR imaging, caused by low proton density, susceptibility effects, and cardiac and respiratory motion artefacts, impair the image quality. Following technical advances of high-performance gradients, phased-array receiver coils and refined imaging sequences, high field MRI systems are becoming clinically available for pulmonary imaging [7]. Recent studies demonstrated its capability for imaging a variety of lung diseases compromising focal lung lesions, diffuse infiltrative lung disease and metastases [8][9][10].…”
Section: Introductionmentioning
confidence: 99%